1978
DOI: 10.1093/jn/108.10.1606
|View full text |Cite
|
Sign up to set email alerts
|

Starvation and Refeeding in Rats: Effect on Organismic Respiration, Cytoplasmic Constituents of Liver, and Succinic Dehydrogenase Activity in Liver, Kidney, and Heart

Abstract: An analysis of starvation and starvation followed by refeeding was undertaken to characterize some organismic, organ, and mitochondrial responses to these two circumstances. Body weight, organismic respiration as well as weight protein and succinic dehydrogenase activity for liver, kidney, and heart were determined over the course of 6 days of starvation and 5 days refeeding for adult male rats. Assays of marker enzyme activities for mitochondria (cytochrome oxidase), lysosomes (acid phosphatase), endoplasmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…RIBF,,,,,. and MBF,,,, were also similar for groups A, B and D, but differed for rats in groups C and E. _____ return in resting metabolic rates to the exact prestarvation value for both humans (Grande et al 1958) and rats (Cascarano et at. 1978).…”
Section: I S C U S S I O~mentioning
confidence: 86%
“…RIBF,,,,,. and MBF,,,, were also similar for groups A, B and D, but differed for rats in groups C and E. _____ return in resting metabolic rates to the exact prestarvation value for both humans (Grande et al 1958) and rats (Cascarano et at. 1978).…”
Section: I S C U S S I O~mentioning
confidence: 86%
“…Whereas no significant differences in the relative fat content were found among the three groups, expectedly, RES rat livers contained significantly less glycogen than AL livers [ 11 ]. Earlier observations in older rats have shown that the livers generally maintained similar amounts of cells in RES, AL and CU [ 42 ], implying that the size of RES liver cells was half of the AL cells with minimal levels of glycogen [ 11 ]. Yet, we also found that the RES cells accumulated 7 % of new proteins mostly in the mitochondria, to drive the catabolism of carbohydrates, lipids and proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondria play an important role in fatty acid oxidation and changes might be expected in fasting where increased myocardial utilisation of fatty acids occurs. Cascarano et al (1978) studied the effects of fasting of rats for up to 6 days on certain mitochondria1 enzymes. Whereas succinic dehydrogenase activity in liver and kidney fell steadily, that in the heart doubled at 2 days and fell to normal values by 4 days.…”
Section: Correlation With Biochemical Changesmentioning
confidence: 99%